Principle of financial adequacy of local self-government units vs. local self-government healthcare expenditures - Karczewska, Zofia M.; Mielech, Ewelina (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The economic crisis caused by the pandemic revealed problems related to the financing of the tasks of local government units (LGUs). Moreover, these problems are associated with the violation of the constitutional principle of adequacy in financing public tasks, including tasks related to health protection. Aim: The implementation of the principle of financial adequacy of local government units based on an analysis of local government spending on health care, considering the current situation caused by the COVID 19 pandemic. Results: The results from the analysis of finances confirm that local governments’ concerns about their financial situation are justified. The decrease in the investment potential of communes and poviats, dynamically growing current expenses, and the apparent increase in total income are the fundamental causes of the analysis. These causes, concerning the diversified number of medical entities in the analyzed cities’ self-government, confirm that the principle of financial adequacy in health care is strongly undermined. Besides, the economic situation caused by the COVID 19 pandemic has highlighted financial and organizational problems in local government units.